PRECIPITATION KINETICS AND CARBON ISOTOPE PARTITIONING OF INORGANIC SIDERITE AT 25°C AND 1 ATM - Jimenez-Lopez C.; Romanek C.S. (My University, 2004)
Siderite was precipitated from NaHCO3 and Fe(ClO4)2 solutions under anaerobic conditions at 25°C and 1 atm total pressure using a modified version of the chemo-stat technique and the free-drift technique. Samples of solution and solid were withdrawn at different time intervals during time course experiments to determine the bulk and isotope composition of the solution and solid, and the morphology and mineralogy of the solid. A series of metastable precursors precipitated and dissolved sequentially, culminating in well-crystallized siderite rhombohedra having an average edge of ~ 2 μm and a limited size distribution. Siderite precipitation rate ranged from 100.23 to 102.44 μmol*m-2*h-1 for saturation states (with respect to siderite) ranging from near equilibrium to 103.53. Calculated carbon isotope fractionation factors (103lnα) averaged 8.5 +/- 0.2 (1σ n = 4) for the siderite-CO2(g) system and 0.5 +/- 0.2 (1σ n = 4) for the siderite-HCO3-(aq) system.
Keywords: siderite